Collaboration during a crisis – the Lighthouse Lab volunteers. Issue 7 (28th July 2020) - Ulhuq, Fatima R.; Berry, Sophia K.; Kelly, Lucy; Stansfield, Ben; Deal, Anna; Lester, Harriet
Abstract : As a group of early-career researchers, we recount our experiences of volunteering at one of the national Lighthouse Labs based at the UK Biocentre in Milton Keynes. We worked together as part of a multidisciplinary team to support the large-scale processing of coronavirus disease 2019 (COVID-19) swabs from across the whole of the UK.